Isolation and purification of active opioid receptors from rat brain - Wang Feng; Chi Zhi-Qiang (Acta Pharmacologica Sinica, 2016)
Active opioid receptor was purified to apparent homogeneity from rat brain membranes. The purification was accomplished in two steps: Vicia bungei Ohwi lectin-sepharose affinity chromatography followed by 6-succinylmorphine-(CH2)6-sepharose affinity chromatography. The purified receptor had a molecular weight of 45 000 as determined by SDS-PAGE and was judged to be homogeneous and genuine opioid receptor by the following criteria： (1) and (2) the Na125I andβ-[125I]endorphin labeled protein was analysed by SDS-PAGE separately and a single band was detected in both； (3) a single band was shown in the gel of isoelectric focusing and (4) the purified protein bound with [3H]etorphine in a stereospecific and saturable manner.